Vous êtes sur la page 1sur 3
ere nd

ere

nd

1 2 m 1 m 2

v 1

1

v 2 2

v 1

> 0

v 2

< 0

v 2

1 v

v 2 v 1

1 v

v 2

k = m 1 /m 2

v 2 v 1 1 v ′ ′ v 2 k = m 1 /m 2

v 1 = v 2

k = 1 v

1 v

2

v 1 >> 1 v 2 0

k >> 1

v

1 v

2

v 1 >> 1 v 2 0

k << 1

v

1 v

2

1 v 2 ≈ 0 k << 1 v ′ 1 v ′ 2 R m

R m 1

m 2

2

1

e x

f

v

1

f

v

2

1 2

e

e T e T

e T e

µ = m 1 /m 2

v

v i

i

1

v 1 i = v 1 i . e

x

v

2 v 0

2 =

i

i

i

1t v 2t

v i

1n

v

i

2n

v

1

f

f

i

v

2

f

f

1t v v 2t v

v

v f

f

f

1t = v 1t

f

2t = v

i

2t

1n v 2n

e T e

e T e

θ R H

e T e e x e

y

e x e y

v

f

1

v

f

2

=

=

v 1 i . µ +

cos2 θ 1 + µ

e x + v i

1 . sin 2 θ

µ + 1

e

y

1 . µ(1 cos2 θ )

v i

µ + 1

e x v i

1 . µ sin 2 θ

µ + 1

e

y

m 1 = m 2 o

v 1 i H m 1 m 2

15 o m 1 = m 2 v i

1 = 10 cm.s 1

m 1 = m 2 v i 1 = 10 cm.s − 1 m 1 m

m 1

m 2

z max

z max v 1 m 1 m 2

o

43 .9 o

g = 10

C

cu

p

= 0 .385 J.Kg 1 .K 1